1983
DOI: 10.3168/jds.s0022-0302(83)81783-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Edema of the Mammary Gland in Primigravid Dairy Heifers

Abstract: The severity and anatomical extent of mammary edema (edema) of 73 primigravid Holstein heifers was scored, and certain hormones in peripheral blood plasma were quantified. The objective was to obtain by least-squares analysis of covariance independent estimates of the association of each hormone and other factors with edema scores around first calving. Mammary edema prepartum increased with age of heifer and gestation length, decreased as calf birthweight increased, but was unrelated to seasonal fluctuations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 13 publications
0
12
0
2
Order By: Relevance
“…Cows with longer gestation length showed increased severity of edema (Malven et al, 1983). Malven et al (1983) also reported an association of higher plasma concentrations of estradiol-17α and estrone with increased severity of edema. Melendez et al (2006) reported that milk yield at the first DHIA test day was 3.6 kg lower in cows with UE.…”
Section: Short Communicationmentioning
confidence: 88%
See 1 more Smart Citation
“…Cows with longer gestation length showed increased severity of edema (Malven et al, 1983). Malven et al (1983) also reported an association of higher plasma concentrations of estradiol-17α and estrone with increased severity of edema. Melendez et al (2006) reported that milk yield at the first DHIA test day was 3.6 kg lower in cows with UE.…”
Section: Short Communicationmentioning
confidence: 88%
“…Cows, particularly entering the first lactation, generally have some UE in late pregnancy and at parturition, but extensive edema has been shown to affect milk production and health of the udder (Malven et al, 1983). Cows with longer gestation length showed increased severity of edema (Malven et al, 1983). Malven et al (1983) also reported an association of higher plasma concentrations of estradiol-17α and estrone with increased severity of edema.…”
Section: Short Communicationmentioning
confidence: 99%
“…Fatores hormonais endógenos parecem contribuir para o desenvolvimento do edema de mama. Conforme destacam Malven et al (1983), em novilhas da raça holandesa preta e branca, o Estradiol 17 a e a Estrona promoveram e/ou aumentaram a severidade do edema de mama antes do parto, ao passo que a progesterona e o estradiol 17 b desfavoreceu-o no pré-parto. Ainda segundo os autores, o estradiol 17 b evitou o favorecimento da manifestação do edema de mama em vacas, logo após o parto.…”
Section: º) Outros Fatores Implicadosunclassified
“…However, if edema is sufficiently severe it can interfere with suckling by the calf, milking, and may cause other complications including udder inflammation. Edema is caused by excessive accumulation of fluid underneath the skin and at least some mammary edema is associated with pregnancy and parturition, especially in primigravid heifers (Malven et al, 1983).…”
Section: Udder Edemamentioning
confidence: 99%